2017
DOI: 10.1136/emermed-2015-205517
|View full text |Cite
|
Sign up to set email alerts
|

The Royal College of Emergency Medicine composite pain scale for children: level of inter-rater agreement

Abstract: The Ladder score could be omitted from this composite tool as it has poor inter-rater agreement in comparison with the other indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Of 65 scales, 32 (49%) were validated to assess acute pain, 4,11,12,14,[16][17][18][19][20][21][24][25][26][27]29,[32][33][34][35]37,38,[41][42][43]45,[52][53][54][55][56]60,61,64,67,[70][71][72][73][74]76,79,84,89 14 (22%) to assess prolonged pain, 4,13,15,22,24,[28][29][30]35,[37]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 65 scales, 32 (49%) were validated to assess acute pain, 4,11,12,14,[16][17][18][19][20][21][24][25][26][27]29,[32][33][34][35]37,38,[41][42][43]45,[52][53][54][55][56]60,61,64,67,[70][71][72][73][74]76,79,84,89 14 (22%) to assess prolonged pain, 4,13,15,22,24,[28][29][30]35,[37]…”
Section: Resultsmentioning
confidence: 99%
“…Of 65 scales, 42 (65%) were behavioral scales 11,13,15,[18][19][20]22,26,[28][29][30]32,34,35,46,47,[52][53][54][55][56][58][59][60][61][62][63][64]66,67,[70][71][72][73][74][75][76][77][78][79][80][82][83][84][85][86][87][88]91 and 23 (35%) were multidimensional scales 4,12,14,16,17,<...…”
Section: Resultsmentioning
confidence: 99%
“…The 40 studies are grouped and displayed under the 4 dyads: child vs caregiver (n = 30), 2 , 4 11 , 13 , 15 , 18 , 19 , 23 , 27 , 31 , 34 , 36 , 39 , 41 , 43 , 44 , 48 , 53 , 54 , 56 , 57 , 61 , 64 , 67 child vs HCP (n = 17), 8 , 11 , 13 , 14 , 16 , 23 , 31 , 35 , 41 , 44 , 46 , 51 , 53 , 54 , 57 , 60 , 64 caregiver vs HCP (n = 10), 8 , 11 , 13 , 23 , 41 , 44 , 53 , 54 , 64 , 67 and nurse vs other HCPs (n = 5). 17 , 21 , 26 , 35 , 59 Fifteen studies examined more than one dyad (Appendix B, available at http://links.lww.com/PR9/A168 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results were not statistically pooled. Two studies using ICC or weighted kappa were highly discordant (ES 5 0.17 26 and 0.87 59 ). One study that used a Pearson correlation showed a high ES (ES 5 0.90 35 ).…”
Section: Consistency Of Pediatric Pain Ratings Between the Nurse And ...mentioning
confidence: 97%
“…RCEM recommends the use of the attached assessment tool or a locally developed alternative. The Ladder element (which included a 0-10 numerical rating scale) of the scale has been removed following evidence suggesting limited advantage to this section (8) .…”
Section: Pain Assessmentmentioning
confidence: 99%